Analysis of Production Factor Efficiency in Organic Rice Farming (Oryza sativa) (A Case in Sukorejo Village, Sambirejo Sub-district, Sragen District) - Novil Dedy Andriatmoko (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
Central Java Province is the third largest rice producer in Indonesia (BPS, 2019). Sragen Regency has started developing organic rice since 2010 and the slogan for agriculture is